2020
DOI: 10.1111/sdi.12889
|View full text |Cite
|
Sign up to set email alerts
|

Preventive care for patients with end‐stage kidney disease: crossroads between nephrology and primary care

Abstract: Patients with end‐stage kidney disease (ESKD) undergoing maintenance hemodialysis (HD) might expect their nephrologists to coordinate all their healthcare needs. We performed a survey among adult patients with ESKD undergoing HD in two outpatient dialysis centers at the University of Florida to identify differences in characteristics between patients with and without primary care providers (PCP) and to explore the association of PCP utilization with adherence to preventive health measures. Of the 132 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…As hemodialysis patients are mostly managed by medical specialists, primary health care utilization might be underrepresented. In line with this assumption, a recent study confirmed that dialysis patients that are also treated by a primary care physician, were significantly more likely to receive influenza vaccination [24]. Most frequent arguments against influenza vaccination included the fear of side effects and allograft injury.…”
Section: Discussionmentioning
confidence: 80%
“…As hemodialysis patients are mostly managed by medical specialists, primary health care utilization might be underrepresented. In line with this assumption, a recent study confirmed that dialysis patients that are also treated by a primary care physician, were significantly more likely to receive influenza vaccination [24]. Most frequent arguments against influenza vaccination included the fear of side effects and allograft injury.…”
Section: Discussionmentioning
confidence: 80%
“…Underlying differences in sociodemographic characteristics (e.g., race, ethnicity, income, immigration status) are associated with disparities in CKD care (e.g., patient engagement in healthcare, care seeking, and access to providers) which are reflected in a cascade of disparities in ESKD care, 64,65 including timely receipt of patient education, [66][67][68] health services, 68,69 clinical outcomes (including mortality 70 ), and access to transplantation. [71][72][73][74] For patients with ESKD, nephrologists and dialysis facilities are a common temporary source of care for general health maintenance, 10,37 but the growing prevalence of kidney disease 4,5 along with the shrinking nephrology workforce 75,76 suggest that this type of care substitution is not a sustainable approach for optimizing dialysis and overall care for patients with ESKD.…”
Section: F I G U R Ementioning
confidence: 99%
“…33,35,36 General trends in primary care among patients with ESKD differ by type of service and have been reported elsewhere. 10 While patients reporting concurrent PCP care also reported higher rates of vaccination and preventive screening (e.g., depression, hypertension), 37 observational studies from administrative claims data have found no utilization or survival advantages associated with PCP continuity for non-dialysis care among dialysis patients. 38,39 The safety, cost, and effectiveness of ESKD care are also greatly impacted by the number of systems of care in which patients with ESKD must engage.…”
Section: Fragmentation Of Care As a Barrier Of Optimal Patient-centered Eskd Carementioning
confidence: 99%